2013
DOI: 10.1371/journal.pcbi.1002865
|View full text |Cite
|
Sign up to set email alerts
|

The Underlying Molecular and Network Level Mechanisms in the Evolution of Robustness in Gene Regulatory Networks

Abstract: Gene regulatory networks show robustness to perturbations. Previous works identified robustness as an emergent property of gene network evolution but the underlying molecular mechanisms are poorly understood. We used a multi-tier modeling approach that integrates molecular sequence and structure information with network architecture and population dynamics. Structural models of transcription factor-DNA complexes are used to estimate relative binding specificities. In this model, mutations in the DNA cause chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…Other recent explorations following the same philosophy, such as the deterministic model of gene expression developed by Pujato et al. (), also demonstrate the value of mechanistic models that capture multiple aspects of gene effects. We expect that our ENTWINE model will allow the investigation of many novel questions about the evolution of robustness and phenotypic variability.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Other recent explorations following the same philosophy, such as the deterministic model of gene expression developed by Pujato et al. (), also demonstrate the value of mechanistic models that capture multiple aspects of gene effects. We expect that our ENTWINE model will allow the investigation of many novel questions about the evolution of robustness and phenotypic variability.…”
Section: Discussionmentioning
confidence: 87%
“…; Pujato et al. ). However, few evolutionary models have considered noise, and most of the exceptions (Ciliberti et al.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Computational models such as the gene regulatory network evolution model (also known as the Wagner model), that combine a complex genotype-phenotype mapping (describing a gene regulatory network) with evolutionary dynamics have previously been used to address a range of questions concerned with evolution of biological complexity [33, 34]. In previous studies, the gene regulatory network evolution model has been extended to account for different system levels, including transcription factor (TF)-DNA binding interactions [35] and protein-protein interactions (PPI) [36] at the microscopic level, or between two different populations [10] at the macroscopic level. These previous studies [10, 36] showed how robustness and evolvability can evolve to be distributed across different system levels, depending on the model conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The core GRNs that control the developmental fates of diverse cells are composed of specific sets of transcription factors (TFs), epigenetic regulators, signaling mediators, and post‐transcriptional regulators that include noncoding regulatory RNAs. These GRN components dynamically regulate each other in different regulatory loops to confer robustness to cell fate decisions . Thus, rewiring/reprogramming of cellular GRNs is expected to render different cell fates interchangeable.…”
Section: Introductionmentioning
confidence: 99%